Social Capital's Impact on College Graduation Rates, Debt, and Student Loan Defaults. (August 2022) - Joanis, Steve; Burnley, James; Mohundro, J. D.
This study extends the literature on education economics and student retention by examining social capital as a predictor of college graduation rates, student debt levels, and student loan default rates. Coleman's social capital theory is employed to understand how social influences can impact students through external social support (i.e., social capital). The study uses school-level data from the U.S. Department of Education's Integrated Postsecondary Education Data System and two social capital measures. Results suggest that social capital, at both the state and the community level, significantly influences graduation rates, student debt levels, and loan default rates. Implications for theory and practice are discussed.